Determinan Perilaku Pembelian Paket Umroh: Pendekatan Pemasaran Islam - Ligery, Finny; Aisiyah, Nasyiatul; setiawan, Agus (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the determinants of purchasing behavior for umrah travel packages among the community of Tanjung Raya District, Mesuji Regency, focusing on the influence of service quality and price within the framework of Islamic marketing. The Islamic marketing approach is adopted to ensure that promotional activities and service offerings comply with Sharia principles grounded in the Qur’an. This study employs a quantitative method with an explanatory design to examine the relationship between independent and dependent variables through instrument testing, statistical analysis, and hypothesis testing using SPSS. The sample consists of 100 respondents who have previously purchased umrah packages, selected through purposive sampling. The findings indicate that service quality has a positive and significant effect on purchasing decisions for umrah packages. Price also demonstrates a positive and significant influence on purchasing decisions. Simultaneously, both variables contribute significantly to shaping consumers’ purchasing behavior. These results highlight that prospective pilgrims’ decisions are largely determined by the reliability of the services offered and the affordability of prices relative to their economic capacity. The study provides practical implications for umrah travel providers to consistently implement Islamic marketing principles to ensure trustworthiness and enhance public confidence.